The effectiveness of using blended learning (i-Learn) / Nur Zurain Hasman Hadi...[et al.] - Hasman Hadi, Nur Zurain; Shaifol Azman, Nur Sakinah; Safari, Nor Shahirah; Ridzuan, Abdul Rauf; Ramlan, Aini Faezah (Faculty of Communication & Media Studies, 2020)
Blended learning in general is a program that designed for students which is combination face-to-face and online learning. The aim of this study is to investigate the effectiveness of using blended learning (i-Learn) among students in UiTM Melaka. An online questionnaire with 11 items at demographic section and 20 items was designed to evaluate the aspect of blended learning. The study involved of 200 respondents of UITM Melaka which are from Alor Gajah, Bandaraya Melaka and Jasin campus by using Google Form platform. The amount of survey calculated based on Krejcie and Morgan Table, N=210, S=132. There are three elements designed in the research to measure the effectiveness of using blended learning (i-Learn) among students in UiTM Melaka which are time management, study achievement and social interaction. All variables were measured through scales previously used by other researchers. SPSSS ver. 20 software was used in the analysis and the results of the SPSS indicated that the main factor of using blended learning is time management (M= 3.08).